Adsorption of Hg(II) and Ag(I) from fuel ethanol by silica gel supported sulfur-containing PAMAM dendrimers: Kinetics, equilibrium and thermodynamics. (15th October 2017) - Song, Xiaoting; Niu, Yuzhong; Qiu, Zhoumin; Zhang, Zaixin; Zhou, Yunzhe; Zhao, Jianjian; Chen, Hou
Abstract: The adsorption properties of silica-gel supported sulfur-containing PAMAM dendrimers (SiO2 -G0-MITC ∼ SiO2 -G2.0-MITC) for Hg(II) and Ag(I) from fuel ethanol were investigated. The effect of contact time, temperature, and initial concentration of metal ions on the adsorption was investigated by batch method. Kinetic adsorption can be well depicted by pseudo-second-order model and was controlled by film diffusion process. Isotherm adsorption indicated that the adsorption capacities were promoted by high temperature and initial concentration of metal ion. The adsorption process was appropriate to described by Langmuir model, and carried out by monolayer behavior. The mean free energy calculated from D-R isotherm model implied that the adsorption process was preceded by chemical adsorption mechanism. Thermodynamic parameters demonstrated that the adsorption process was exothermic, spontaneous, and random increasing process.